Cinza vegetal como corretivo e fertilizante no cultivo de capim-marandu em solos do cerrado mato-grossense - Bezerra, Maria Débora Loiola (2013)
The vegetable ash is one alternative of fertilizant and corrective of soil positively influencing the production of marandu grass. The objective was to evaluate the response of Brachiaria brizanta cv. Marandu to the application of vegetable ash in two class of soils (Oxisol and Ultisol). The experiment was conducted in a greenhouse in the period December 2012 to May 2013. The experimental design was completely randomized in a 2x6 factorial, corresponding to two classes of soils (Oxisol and Ultisol) and six doses of vegetable ash (0; 3; 6; 9; 12 and 15 g dm-3) and six replications. We used pots with soil volume of 5 dm3 with five plants. Were made three cuts in shoot of the plants in an interval of 30 days and by occasion of each cutting was evaluated height plant, number of leaves and of tillers; shoot dry mass of leaves, stems and root (only in the third and last cut); leafs/stems ratio; SPAD reading; pH of the soil by occasion of planting and of cuts marandu grass. The results were submitted to analysis of variance by F test and when significant, the qualitative factors (soil classes) submitted to the Tukey test and the quantitative factors (doses of vegetable ash) submitted to regression analysis, both 5% probability, using the Statistical Program SISVAR. The marandu grass, in general, presented greater results in development, growth and yield when grown in Ultisol fertilized with the dose of 15 g dm-3 of vegetable ash, whereas in Oxisol were obtained in the interval of doses of vegetable ash of 9-15 g dm-3.